Learning to learn project at the 6th military police college of Paraná - Demarco, Teresa Raquel Conte; Paracena, Fernanda Pessoli Andreazza (Seven Editora, 2023)
Report: This article reports on how the Learning to Learn project was carried out at the 6th Military Police College in Pato Branco, Paraná. The aim of this project was to intervene in order to work on psychoeducation regarding daily study, routine organization and study techniques. To apply this project, the academic held meetings with groups of previously selected students, using observations, techniques, dynamics and tests to analyze their abilities, learning characteristics and awareness of the importance of study. Results achieved: At the end of the project, it was verified that the initial objective was achieved, in terms of imparting knowledge on the subject, however the result is not immediately measurable, as the effects will be achieved gradually, as the students include this new study habit. DOI:https://doi.org/10.56238/sevened2023.006-097